A checklist of the birds of the Botanical Gardens of Bogor, West Java - Balen, Bas van; Margawati, E T; ., Sudaryanti (KUKILA, 1988)
The avifauna of the Botanical Gardens at Bogor has long attracted ornithologists, both among resident scientists and among newcomers whose first encounters with Javan birds took place here. The present checklist briefly enumerates the bird species observed in the Gardens during the past twenty years. Only a brief discussion is given concerning decreases in some species, as this is discussed more fully in van Balen et al. (1986) and Diamond et al.(1987)